Change in Smoking Outcome Expectation Scale and Anti-Smoking Self-Efficacy Scale of the Students During University Education: Repeated Cross- Sectional Study - Kurçer, Mehmet Ali; Bektaş, Merve; Katar, Ebru (Addicta: The Turkish Journal on Addictions, 2025)
Adolescents are more likely to smoke when they exhibit negative attitudes toward anti-smoking and have low self-efficacy to avoid smoking. This study aims to evaluate changes in the prevalence of smoking, smoking outcome expectations (positive/negative), and anti-smoking self-efficacy among students during their four-year university education. About 435 students who started university in 2018 and graduated in 2021 comprised the participants of this repeated cross-sectional study. The Smoking Outcome Expectation Scale and Anti-Smoking Self-Efficacy Scale were used to assess smoking opposition. The prevalence of smoking among students tends to increase from the first year to the fourth year of education. The rate of students fighting against smoking significantly increases from the first year (45%) to the second year (49.3%) but decreases in the fourth year (42.8%) (p < .05). Negative smoking outcome expectations show a significant increase after the first year in all departments (p < .001). Self-efficacy to resist social influences to smoke decreases significantly in engineering and social sciences in the final year of university (p < .001). Despite the increasing negativity in students’ smoking outcome expectations, the decrease in anti-smoking self-efficacy and the decline in students’ support for anti-smoking measures are reflected in the increase in smoking prevalence throughout university education. These findings indicate the necessity of implementing measures to protect students from starting smoking from the beginning to the end of university education.
Keywords: Anti-smoking self-efficacy; anti-smoking; smoking in university; smoking outcome expectation